2015
DOI: 10.1021/acs.jpclett.5b02378
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Ion Packing on the Dynamics of Ionic Liquids during Micropore Charging

Abstract: Molecular simulations of the diffusion of EMIM(+) and TFSI(-) ions in slit-shaped micropores under conditions similar to those during charging show that in pores that accommodate only a single layer of ions, ions diffuse increasingly faster as the pore becomes charged (with diffusion coefficients even reaching ∼5 × 10(-9) m(2)/s), unless the pore becomes very highly charged. In pores wide enough to fit more than one layer of ions, ion diffusion is slower than in the bulk and changes modestly as the pore become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 49 publications
10
85
1
1
Order By: Relevance
“…This is even clearer in Figure S4 in which we plot the diffusion coefficients as a function of the total pore population. This result is rather counter-intuitive and previous experiments 13 and simulations 19,20 have shown a reverse trend. It is important to note however that previous correlations were done with a given electrolyte-carbon combination and the changes in populations were due to an applied potential difference.…”
Section: Effect Of the Anion Size On The Confined Propertiescontrasting
confidence: 64%
“…This is even clearer in Figure S4 in which we plot the diffusion coefficients as a function of the total pore population. This result is rather counter-intuitive and previous experiments 13 and simulations 19,20 have shown a reverse trend. It is important to note however that previous correlations were done with a given electrolyte-carbon combination and the changes in populations were due to an applied potential difference.…”
Section: Effect Of the Anion Size On The Confined Propertiescontrasting
confidence: 64%
“…is consistent with a recent MD study of an ionic liquid inside slit-pore electrodes. 18 A further MD study on disordered electrode structures revealed changes of D in-pore with voltage on the same order of magnitude as those observed here (though the charging mechanism, and thus in-pore populations differed for their system). 23 The dependence of D in-pore on the in-pore ion population has important consequences for supercapacitor charging rates.…”
supporting
confidence: 73%
“…Theoretical studies based on molecular dynamics (MD) and meanfield theories have shown that ion-ion interactions, ion-carbon interactions and the electrode pore size all influence the rates of ionic diffusion in supercapacitor electrodes, 16,18,23,24 though there is not yet a clear consensus on which factors are most important, nor the order of magnitude by which diffusion is influenced by confinement and by charging. Experimental methods to directly probe inpore motion in an ion-selective and electrode-selective way have until now been lacking.…”
mentioning
confidence: 99%
“…Our findings may have important practical implications. It is known that ordered phases typically exhibit sluggish dynamics, particularly ordered (or quasi-ordered) ionic liquids in slit nanopores [20,44,45]. The knowledge of the parameter space corresponding to such phases may guide to avoid a potential slowdown of charging.…”
Section: Discussionmentioning
confidence: 99%